2011
DOI: 10.4103/0019-5154.87124
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor-alpha in patients with alopecia areata

Abstract: Background:Alopecia areata (AA) is a common form of localized, nonscarring hair loss. It is characterized by the loss of hair in patches, total loss of scalp hair (alopecia totalis, AT), or total loss of body hair (alopecia universalis, AU). The cause of AA is unknown, although most evidence supports the hypothesis that AA is a T-cell-mediated autoimmune disease of the hair follicle and that cytokines play an important role.Aims:The aim of the study was to compare the serum levels of tumor necrosis factor-alph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
3
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 15 publications
6
41
3
3
Order By: Relevance
“…Blockade of TNFα has clear therapeutic benefit in some autoimmune diseases, particularly psoriasis [180]. TNFα is expressed in both lesions [181] and sera of patients with AA [182], but notably, TNFα inhibitors have been shown to have little effect on AA and may even be associated with AA development in some individuals [183,184]. The data suggest TNFα plays a rather more complicated role in AA pathogenesis than was previously thought and may even have some protective function [181].…”
Section: Targeting Cytokine Signalingmentioning
confidence: 55%
“…Blockade of TNFα has clear therapeutic benefit in some autoimmune diseases, particularly psoriasis [180]. TNFα is expressed in both lesions [181] and sera of patients with AA [182], but notably, TNFα inhibitors have been shown to have little effect on AA and may even be associated with AA development in some individuals [183,184]. The data suggest TNFα plays a rather more complicated role in AA pathogenesis than was previously thought and may even have some protective function [181].…”
Section: Targeting Cytokine Signalingmentioning
confidence: 55%
“…(28) ise çalışmalarında TNF-α düzeyi ile Alopesi areata arasında bir ilişki gösterememekle birlikte hastalığın kliniği ile aralarında TNF-α'nın da bulunduğu sitokinler arasında anlamlı bağlantılar olduğunu tespit etmişlerdir. Kasumagic-Halilovic ve arkadaşları ise sınırlı sayıda olgu üzerinde yaptıkları çalışmalarında TNF-α düzeyi ile Alopesi areata arasında ilişki bulmuşlardır (19). Tüm bu çalışmalar, TNF-α serum düzeyinin direkt hastalığın ortaya çıkmasından ziyade hastalı-ğın klinik seyrini etkileyebileceği ya da hastalık sürecinde cevap olarak TNF-α yüksekliği olabileceği fikrini doğurmakla birlikte Alopesi areata ile TNF α arasındaki olası ilişkiye dair net bir veri bulunmamaktadır.…”
Section: Discussionunclassified
“…Alopesi Areata'nın T-hücre aracılı inflamatuar sürecinde TNF-α'nın yer alması (6), anti-TNF kullanımı sırasında Alopesi Areata gelişmesi (22), Alopesi Areata'lı bireylerde TNF α düzeyinin yük-sek bulunması (16,19), TNF-α genindeki -308 G/A polimorfizminin genin ekspresyon düzeyi ile ilişkilendirilmesi (14,15), üstelik TNF-α-308 G/A polimorfizminin Alopesi Areata gibi inflamatuar hastalıkla ilişkili olması (20) ayrıca polimorfizmlerin ırklar ve etnik gruplar arasında farklılık göstermesinden (23) dolayı, Türkiye populasyonunda Alopesi Areata ile TNF-α-308 G/A polimorfizmi arasındaki muhtemel bağlantının belirlenmesi amacıyla bu çalışma planlandı.…”
Section: Introductionunclassified
“…Kasumagic E, et al conducted a study in 36 patients of AA with 20 Controls in which they found that the patients with AA had significantly increased TNF alpha levels in comparison to the levels found in Controls [13]. Working on the same principle Gorcey, et al had achieved improvement in a case of recalcitrant alopecia universalis with the use of TNF alpha antagonist [14].…”
Section: Discussionmentioning
confidence: 99%